2017
DOI: 10.3390/pathogens6040056
|View full text |Cite
|
Sign up to set email alerts
|

Italian Physicians’ Opinions on Rotavirus Vaccine Implementation

Abstract: Rotavirus (RV) infection is the main cause of severe acute gastroenteritis (GE) in the pediatric population and has a major impact in both developing and industrialized countries. The reduction of severe RVGE cases, followed by death or hospitalization, is considered the main benefit of RV vaccination, even though its implementation often faces obstacles. In Italy, the recently approved National Immunization Plan aims to overcome the differences among regions, offering a universal free RV vaccination. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…These findings confirm those obtained by Signorelli et al, who studied the introduction of meningococcal serogroup B vaccine in Italian regional immunization schedules: they found that the lack of health education and communication activities and the economic sustainability in a context of deprived resources are main barriers to the implementation process (23). Moreover, the results of Mita et al, who studied rotavirus vaccine implementation after the approval of the PNPV, are consistent with our findings (24). Some of our respondents suggested that the ANC booklet should be updated with information about immunizations needed in the antenatal period, and this had also been suggested in other studies (12).…”
Section: Discussionsupporting
confidence: 92%
“…These findings confirm those obtained by Signorelli et al, who studied the introduction of meningococcal serogroup B vaccine in Italian regional immunization schedules: they found that the lack of health education and communication activities and the economic sustainability in a context of deprived resources are main barriers to the implementation process (23). Moreover, the results of Mita et al, who studied rotavirus vaccine implementation after the approval of the PNPV, are consistent with our findings (24). Some of our respondents suggested that the ANC booklet should be updated with information about immunizations needed in the antenatal period, and this had also been suggested in other studies (12).…”
Section: Discussionsupporting
confidence: 92%
“…Both Rotarix and Rotateq are available on the market and their administration is not mandatory. In addition, a debate about the benefits of anti-RVA vaccination is still ongoing among physicians [19]. For these reasons, the anti-RVA vaccination coverage in Italy is still low (8%) and not homogeneous among the different Italian regions (range: 0–40%), which have autonomy in the decision about non-mandatory vaccinations and started the programmes at different times [20].…”
Section: Introductionmentioning
confidence: 99%
“…In a survey conducted in Italy in 2015 among family pediatricians, 76.2% of respondents declared that they were convinced on the value of RV vaccination and 57.4% of them stated that they recommended it in their daily practice; however the adherence to RV vaccination was estimated to be <25% due, in the greatest part (60.4%), to poor confidence in the vaccine. 6 In a more recent web-based survey, more than 85.8% of one thousand family pediatricians spontaneously declared that they would recommend RV vaccination in the future, however more than 40% of them feared that a recommended but not compulsory vaccination might exert a negative impact on family acceptance. 7 On the other side, although surveys carried out among Italian parents documented significant parental distress due to rotavirus gastroenteritis (RVGE) hospitalization (93.6% reporting high/medium stress), many parents were still unwilling to immunize their babies for RV due to a lack of knowledge of the rotavirus burden of disease and the possibility of preventing RVGE by vaccination.…”
mentioning
confidence: 99%